The Bear in the back yard : Moscow's Caribbean strategy - Ashby, Timothy (Lexington Books LexingtonUS, 1987)
Argues that the Soviet Union is following a deliberate and increasingly sophisticated strategy in its penetration of the Caribbean region, including Centre America